The given eqn can be written as
log (xy+k) = (x-1)2/2
By differentiating the given expression we get
1/x + 1/y dy/dx = (x-1)(xy+k)
=> x dy/dx = (x2 - x-1)y + k(x-1)
Comparing we get k =1
Thanks Govind & Avinav
If k is a constant such that satisfies the differential equation
, then k may be
(a) 1 (b) 0 (c) -1 (d) -2
ANS : 1
The given eqn can be written as
log (xy+k) = (x-1)2/2
By differentiating the given expression we get
1/x + 1/y dy/dx = (x-1)(xy+k)
=> x dy/dx = (x2 - x-1)y + k(x-1)
Comparing we get k =1
Thanks Govind & Avinav
see..log of xy+k...is not...log x+log y+log k
dis is wer u ve a mistake